Dressing versus non-dressing technique for long-term exit-site care in children on continuous ambulatory peritoneal dialysis: a single-center retrospective cohort study (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND There is no consensus on the optimal long-term exit-site care strategy in children on long-term peritoneal dialysis (PD) worldwide. Thus, this study aimed to compared the dressing versus non-dressing technique for long-term exit-site care to prevent PD-related infection. METHODS This retrospective cohort study involved patients aged <18 years with end-stage kidney disease who were on continuous ambulatory PD at the Cipto Mangunkusumo Hospital between March 2014 and March 2019. Long-term exit-site care was initiated within 3 months after the insertion of Tenckhoff catheter. The patients and caregivers can choose to either maintain the dressing method or change to the non-dressing method for the subsequent long-term exit-site care. The follow-up was performed until the following 6 months. RESULTS Out of 34 patients, 18 were treated without dressing and 16 with dressing technique. The peritonitis rates were 0.17 and 0.06 episodes per year at risk in the non-dressing and dressing groups; the adjusted incidence rate ratio was 0.4 (95% confidence interval = 0.043.25; p = 0.4). Allergic contact dermatitis occurred in 15/18 (83%) patients in the non-dressing group and 11/16 (69%) in the dressing group before long-term exit-site care was applied. Ultimately, no patient in the non-dressing group developed allergic contact dermatitis, whereas 11 (69%) had allergic contact dermatitis in the dressing group at the end of follow-up. CONCLUSIONS Non-dressing technique may increase the risk of peritonitis in children on long-term PD; however, it is beneficial for children vulnerable to allergic contact dermatitis.